EARNING MANAGEMENT DAN CASH HOLDING SEBAGAI MODERASI PENDETEKSIAN WINDOW DRESSING DENGAN F-SCORE ANALYSIS - Niken Savitri Primasari; Endah Tri Wahyuningtyas (Universitas Muria Kudus, 2020)
This research aims to carry out financial report detection and the possibility of window dressing practice with earning management and cash holding leading to the fraudulent financial reporting actions in companies listed on the Indonesia Stock Exchange. Financial statements will be classified according to Altman Z-Score. Action of window dressing is reporting with F-Score, the subsequent treatment of earning management and cash holding as a moderating are to find out the influence of two window dressings to F-Score. The period of research on financial statements will be conducted on a triwulanly basis from 2015-2019.